The dangers of unsafe spray techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
According to the UN Food and Agriculture Organization (FAO), the technology used to spray pesticides in most developing countries reflects technical standards of 40 years ago, resulting in pesticide waste and environmental damage. FAO called for the...